Pengaruh Keamanan terhadap Pengembangan Pariwisata Maritim di Indonesia - Eka Erlinda; Seniwati Seniwati (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
The influence of security on the development of maritime tourism in Indonesia cannot be separated from Changing concepts of security in international relations. Human security, including its economic, food and environmental dimensions, is crucial for the sustainability of the marine tourism sector. Threats such as poverty and human rights violations have a direct impact on this industry, which depends on social and political stability. Managing environmental security threats is essential to ensure the maritime tourism sector can thrive and benefit local communities economically. This ponder employments a subjective approach to analyze security's influence on maritime tourism development in Indonesia. The information appears a critical increment within the number of remote visitor visits. In any case, oceanic security issues, such as robbery and unlawful angling, remain significant challenges that have to be tended to so that Indonesia can draw in more visitors and venture whereas fortifying the nearby economy and coastal communities. The novelty of this study is due to the need for more literature discussing the influence of security on the development of maritime tourism in Indonesia.